How the Biotic Pump links the hydrological and the rainforest to climate : ¿Is it for real? ¿How can we prove it?. (2014)
the Biotic Pump Theory, as set forward by Drs. Makarieva and Gorshkov, states that the primary force driving surface winds, certainly in the tropics, is induced by the negative changes in atmospheric pressure caused by condensation of water vapour when clouds form. A high rate of condensation is necessary and therefore the theory requires that a suffciently high rate of evapotranspiration from large areas of forest provides the "fuel" for the process. The theory therefore runs contrary to the traditional view, as introduced in climate models, that surface winds are the sole products of differences in surface heating as well as of latent heat release during the process of condensation. Indeed, Makarieva and her colleagues claim that transitions in the phases of water play a far more important role in driving atmospheric dynamics than is currently recognised